Learnings from the 2024 Utah Cardiac Recovery Symposium: A Roadmap for the Field of Myocardial Recovery - Muthu Kumar Krishnamoorthi; Konstantinos Sideris; Arvind Bhimaraj; Stavros G. Drakos (Methodist DeBakey Cardiovascular Journal)
The 12th annual Utah Cardiac Recovery Symposium (U-CARS) in 2024 continued its mission to advance cardiac recovery by uniting experts across various fields. The symposium featured key presentations on cutting-edge topics such as CRISPR gene editing for heart failure, guideline-directed medical therapy for heart failure (HF) with improved/recovered ejection fraction (HFimpEF), the role of extracorporeal cardiopulmonary resuscitation (ECPR) in treating cardiac arrest, and others. Discussions explored genetic and metabolic contributions to HF, emphasized the importance of maintaining pharmacotherapy in HFimpEF to prevent relapse, and identified future research directions including refining ECPR protocols, optimizing patient selection, and leveraging genetic insights to enhance therapeutic strategies.